Literasi Tentang Transaksi Jual Beli Yang Sesuai Dengan Nilai-Nilai Islam Pada Siswa PPMTI Tanjung Berulak Kec. Kampar - Khairi, Rifqil; Reza, Saru; Hidayat, Hidayat; Hasda, Mifta; Arif, Muhammad; Amalia, Nala (Journal of Community Sustainability, 2025)
This community service activity was conducted at Pondok Pesantren Madrasah Tarbiyah Islamiah (PPMTI) Tanjung Berulak under the theme “Introduction to Islamic Finance as a Solution for Managing Finances in an Islamic Way.” The aim was to provide 12th-grade students with a basic understanding of Islamic finance concepts and their implementation, particularly through financial institutions such as Islamic banks. Preparations for the activity included coordination with the pesantren, development of materials, and creation of supporting media. The material was delivered through a lecture method, followed by an interactive discussion session that allowed students to ask questions and gain deeper understanding. The results of the activity showed an increase in students’ understanding and enthusiasm for applying Islamic financial principles in their daily lives. This activity not only provided direct benefits but is also expected to shape students into agents of change who promote Islamic financial practices within their communities and contribute to the creation of a more Islamic and prosperous society.